Primary lymphoma of colon: a case report - Çekiç, Cem; Gümüş, Zeynep Zehra; Akay, Hüseyin Sinan; Ünal, Firdes; ÖzdemirkIran, Füsun; Vatansever, Sezgin; Ünsal, Belkis (Medycyna Paliatywna/Palliative Medicine, 2013)
One-third of all extranodal lymphomas are located in the gastrointestinal tract, and 10-20% of gastrointestinal lymphomas are located in the colon. Primary colorectal lymphomas constitute 0.1-0.5% of all large bowel malignancies. The most common type of lymphoma is diffuse large B cell lymphoma. It is twice as common in males than females and generally is encountered in the 6th and 7th decades. Abdominal pain and weight loss are the most common symptoms, and because of these non-specific symptoms, the diagnosis is usually delayed. Isolated surgical therapy or chemotherapy can be employed; also a combination treatment might be preferred. In this case report, we aimed to present a colonic non-Hodgkin lymphoma (NHL) patient who was admitted with weight loss and abdominal pain. Presentation of the case was at an earlier age relative to the literature. Also, we discussed the treatment of the patient.